A group decision-making model for important power user risks based on cloud model and set pair analysis: a case study in China. (9th April 2021) - Liu, Jicheng; Fu, Xiaoxu; Xu, Fangqiu; Yan, Suli
The safe and stable operation of important power users plays an important role in the harmonious development of society and economy. Different from previous studies which mostly based on reliability model, a group decision-making model based on cloud model and connection number is proposed in this paper. First, an assessment index system is established including operation safety risk, cooperation credit risk, power regulation risk and operating capacity risk. Then, with the advantage in dealing with qualitative language, cloud model is employed to convert the qualitative concepts into quantitative values, which reduce the fuzziness and randomness. Next, in order to integrate the information among different index, the geometric operator of binary connection number is defined. Finally, the comparison method of connection numbers is put forward to rank the results. The example and sensibility analysis verify the effectiveness and applicability of the model in this paper.